2011
DOI: 10.1371/journal.pone.0025054
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Promotes Remodeling of Coronary Resistance Vessels

Abstract: Low thyroid hormone (TH) function has been linked to impaired coronary blood flow, reduced density of small arterioles, and heart failure. Nonetheless, little is known about the mechanisms by which THs regulate coronary microvascular remodeling. The current study examined the initial cellular events associated with coronary remodeling induced by triiodothyronine (T3) in hypothyroid rats. Rats with established hypothyroidism, eight weeks after surgical thyroidectomy (TX), were treated with T3 for 36 or 72 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 35 publications
3
41
0
Order By: Relevance
“…These haemodynamic and metabolic factors prevent the increase in HIF-1a and hence the triggering of an angiogenic response mediated by VEGF, bFGF or angiogenin. The greater cardiac capillary density in the hypothyroid group is in agreement with previous findings in rats (Heron & Rakusan 1994, Savinova et al 2011) and rabbits (Tomanek et al 1993). The cardiac capillary response to hypothyroidism is thought to be similar to that of bradycardially paced hearts, in which capillary densities are increased (Tomanek et al 1993.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These haemodynamic and metabolic factors prevent the increase in HIF-1a and hence the triggering of an angiogenic response mediated by VEGF, bFGF or angiogenin. The greater cardiac capillary density in the hypothyroid group is in agreement with previous findings in rats (Heron & Rakusan 1994, Savinova et al 2011) and rabbits (Tomanek et al 1993). The cardiac capillary response to hypothyroidism is thought to be similar to that of bradycardially paced hearts, in which capillary densities are increased (Tomanek et al 1993.…”
Section: Discussionsupporting
confidence: 91%
“…The reduction in myocyte diameter may be responsible for this increase, given that the hypothyroidism-induced myocardial atrophy would bring capillaries closer together, thereby increasing the number of capillaries per square millimetre of tissue. Savinova et al (2011) reported an increased capillary density in the cardiac ventricle of thyroidectomised (TX) female rats that correlated with LV weight when controls and TX rats were pooled in a common regression line. However, TX rats showed a reduction of around 28% in LV weight/body weight ratio and an increase of around 66% in myocardial capillary density.…”
Section: Discussionmentioning
confidence: 99%
“…TRb is required for angiogenesis during cardiac development (32). Thyroid hormones are powerful regulators of vessel overgrowth in the hypothyroid state; they promote coronary arteriolar and capillary growth (33).…”
Section: Mechanism Underlying the Effect Of Thyroid Hormone On The Camentioning
confidence: 99%
“…FITCIsolectin-B4 (IB4; Vector, Burlingame, CA, USA) and Cy3-α-smooth muscle actin (α-SMA; Sigma-Aldrich) were used in combination to label endothelial cells and vascular smooth muscle cells respectively. Arteriolar numeric density (ND), arteriolar length density (LD), capillary ND density, and total capillary length were quantified using previously described methods (34,35).…”
Section: Immunohistochemistry and Immunofluorescencementioning
confidence: 99%